The great potential of dhikr as prevention of coronary heart disease: A review - Abdurachman; Luqman Hakim Andira; Andira, Dzulqarnain; Alkaff, Firas Farisi; Weinheimer, Anita Zara; Dewanti, Adinda Tania (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Dhikr is a form of Islamic prayer that involves repeating certain phrases or words to focus on God's presence. This article proposed the management of coronary heart disease (CHD) through changes in individual character through reminiscence. This review aims to provide an overview of current knowledge on how dhikr practice can affect cardiovascular health. We conducted a systematic search across various databases such as PubMed, Google Scholar, and Scopus, utilizing keywords like